Experiences of Families Caring for Children with Newborn Screening-Related Conditions: Implications for the Expansion of Genomics in Population-Based Neonatal Public Health Programs - Lynn Bush; Hannah Davidson; Shani Gelles; Dawn Lea; Laura M. Koehly (MDPI AG, 2022)
With the expansion of newborn screening conditions globally and the increased use of genomic technologies for early detection, there is a need for ethically nuanced policies to guide the future integration of ever-more comprehensive genomics into population-based newborn screening programs. In the current paper, we consider the lived experiences of 169 family caregivers caring for 77 children with NBS-related conditions to identify lessons learned that can inform policy and practice related to population-based newborn screening using genomic technologies. Based on caregiver narratives obtained through in-depth interviews, we identify themes characterizing these families' diagnostic odyssey continuum, which fall within two domains: (1) medical management implications of a child diagnosed with an NBS-related condition and (2) psychological implications of a child diagnosed with an NBS-related condition. For Domain 1, family caregivers' experiences point to the need for educational resources for both health care professionals that serve children with NBS-related conditions and their families; empowerment programs for family caregivers; training for providers in patient-centered communication; and access to multi-disciplinary specialists. For Domain 2, caregivers' experiences suggest a need for access to continuous, long-term counseling resources; patient navigator resources; and peer support programs. These lessons learned can inform policy recommendations for the benefit of the child, the family, the healthcare system, and society.